Effects of radiation on toxicity, complications, revision surgery and aesthetic outcomes in breast reconstruction: An argument about timing and techniques. Issue 12 (December 2021) - Huang, Y.; Sanz, J.; Rodríguez, N.; Foro, P.; Reig, A.; Membrive, I.; Zhao, M.; Li, X.; Martínez, A.; Algara, M.
Summary: Background: Radiotherapy (RT) combined with breast reconstruction can reduce the risk of cancer recurrence and increase the survival rate. However, this approach seems to worsen aesthetic outcomes and increase complication rates. The impact of breast reconstruction timing and techniques on clinical outcomes, however, remains unclear. For this reason, we aimed to perform a more comprehensive analysis of a series of patients undergoing RT and breast reconstruction. Methods: Patients were divided into 4 groups according to the timing of reconstruction (before RT and after RT) and surgical technique (heterologous reconstruction and autologous reconstruction (AR)). The median time between RT and reconstruction, number of revision surgeries, incidence of complications, toxicity, aesthetics and associated clinical risk factors were used to assess the clinical outcomes. An objective system of skin toxicity evaluation was performed. Results: Ninety-five patients were included in this study. No significant differences in the median time between RT and reconstruction, incidence of complications, toxicity or aesthetics were noted between different timings or techniques of reconstruction. Patients undergoing AR needed more revision surgeries to complete reconstruction. However, the total number of surgical procedures was similar between the groups. In a comparison between the treated and untreated breasts by an objective system, RT produced an increase in erythema and pigmentation and a decrease in elasticity in the treated breast (p<0.05 for all parameters). On multivariate analysis, smoking was a significant predictor associated with complications. Conclusions: Combined breast reconstruction and RT seem to be successful regardless of the order of treatment or the type of reconstruction.